Gambaran Resilience Penderita TB Paru di Puskesmas Perak Timur Surabaya - Asmaul Husna (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2019)
Tuberculosis in the healing process requires considerable time and require the support of the immediate environment, especially the family. The ability of individuals to survive determining the success of a treatment called resilience. The aim of researchers to describe resilience pulmonary tuberculosis patients in Puskesmas East Perak Surabaya. Samples were pulmonary tuberculosis patients amounted to 63 respondents. Engineering samples using Accidental Sampling. Data were analyzed using descriptive qualitative. The variable in this study is resilience pulmonary tuberculosis patients. The instrument used was a questionnaire resilience. Data analysis used Rho Spearman ? = 0.05. The results showed respondents with moderate resilience of 57.1%, 30.2% high resilience and respondents with lower resilience of 12.7%. This shows that the resilience pulmonary tuberculosis patients in the clinic silver east of Surabaya average has medium resilience. Resillience high on Lung penderitaTB affect the emotional support she received from family. So expect the environment around the patient is able to be a positive support system for Penderia pulmonary TB.